Plant Bioinformatics : Decoding the Phyta - Hakeem, Khalid Rehman (Springer, 2020)
1. Introduction to fundamental and applied bioinformatics research in plant life sciences -- Concept, development and application of novel computational methods for the analysis and integration of -omics data -- 3. Impact of high-throughput techniques on plant translational research -- 4. Functional genomics approaches in plant research -- 5. Bioinformatical versus experimental analyses of small RNAs in plants -- 6. Systems analyses of plant functions